121k views
4 votes
F(x) = x2 − 8x + 15 g(x) = x − 3 h(x) = f(x) ÷g(x)

2 Answers

3 votes
hello :
x²-8x+15 = (x-3)(x-5)
h(x) = f(x) ÷g(x) = (x-3)(x-5)/(x-3)= x-5
User Idstam
by
6.1k points
4 votes

Answer:

Explanation:

Given: It is given that
f(x)=x^2-8x+15 and
g(x)=x-3.

To find: The value of
h(x)=(f(x))/(g(x))

Solution: It is given that
f(x)=x^2-8x+15 and
g(x)=x-3, then the value of
h(x)=(f(x))/(g(x)) will be:


h(x)=(x^2-8x+15)/(x-3)


h(x)=(x^2-5x-3x+15)/(x-3)


h(x)=(x(x-5)-3(x-5))/((x-3))


h(x)=((x-3)(x-5))/((x-3))


h(x)=x-5

Thus, the value of
h(x) will be
x-5.

User Eugene Ramirez
by
7.1k points